2011
DOI: 10.1007/s00296-011-1808-z
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination survey in patients with rheumatoid arthritis: a cross-sectional study

Abstract: The objective of this study is to evaluate the vaccination status in rheumatoid arthritis (RA) patients during routine clinical practice, data from a German non-interventional cross-sectional study. In this prospective study, patients with rheumatoid arthritis were interviewed using a standardized questionnaire focusing on vaccination. Available vaccination documents were evaluated, and titers for common vaccination antigens (hepatitis B, rubella, mumps, measles, diphtheria, tetanus) were analyzed with special… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
2
10

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 24 publications
1
16
2
10
Order By: Relevance
“…Because only RA patients in rheumatologic care were included in COMORA, our study confirms this vaccination coverage. The proportion of vaccinated RA patients was, both in COMORA and PROCLAIR, considerably lower than in the second study, where 301 patients were included in a single centre and the reported vaccination rates were between 20.2 and 39.0 % (pneumococcal) and 59.3 and 69.2 % (influenza) for different treatment arms [14]. The higher rates may be explained by higher vaccination awareness in the hospital or within the region.…”
Section: Discussioncontrasting
confidence: 75%
See 2 more Smart Citations
“…Because only RA patients in rheumatologic care were included in COMORA, our study confirms this vaccination coverage. The proportion of vaccinated RA patients was, both in COMORA and PROCLAIR, considerably lower than in the second study, where 301 patients were included in a single centre and the reported vaccination rates were between 20.2 and 39.0 % (pneumococcal) and 59.3 and 69.2 % (influenza) for different treatment arms [14]. The higher rates may be explained by higher vaccination awareness in the hospital or within the region.…”
Section: Discussioncontrasting
confidence: 75%
“…Our study calculated overall vaccination rates of 15.0 % (pneumonia) and 40.8 % (influenza). Two studies have examined the vaccination coverage of subgroups in Germany [14,15]. COMORA studied the vaccination coverage in 3920 RA patients, among them 209 German patients [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25] Não observamos influência da orientação sobre o uso de nenhuma vacina. Entretanto, Doe S et al mostraram melhora da taxa de vacinação contra gripe após otimização da orientação por parte dos profissionais de saúde, com aumento de 56% para 72% em quatro anos de observação.…”
Section: Discussionunclassified
“…The awareness of the possibility to prevent influenza infections and invasive pneumococcal disease by vaccination and the number of effectively performed vaccinations vary within the group of RA patients [6,11].…”
Section: Introductionmentioning
confidence: 99%